Implementation DeLone & McLean IS Success Model for Research and Community Service Management Information System Evaluation - Pratomo, Awang Hendrianto; Agusdin, Riza Prapascatama; Tahalea, Sylvert Prian; Cahyana, Nur Heri (Universitas Pembangunan Nasional Veteran Yogayakarta, 2021)
SRIKANDI is an information system managed by LPPM that manages research and lecturer service within the UPN